Pengaruh Peluang Pertumbuhan, Ukuran Perusahaan, dan Struktur Aset terhadap Keputusan Pendanaan dengan Profitabilitas sebagai Variabel Moderasi - Bornok Yuliarta Pakpahan, Raphita; Gurendraw, Etty; Armeliza , Diah (CV. Publikasi Indonesia, 2022)
This study aims to examine the effect of growth opportunity, company size, asset structure of financial decisions with probability as moderating variable. This research uses secondary data in the form of financial statements of consumer goods sector companies which are listed on the Indonesia Stock Exchange period of 2017-2019. Total of sample in this study is 102 samples from 34 companies. The analytic method used in this study is Moderated Analysis Moderation (MRA) by using SPSS 25 software application. T results show that the growth opportunity, and asset structure have a positive effect on financial decisions, while size company has no effect on financial decisions. Profitability is not able to moderate the relationship between growth opportunity with financial decision, and also, asset structure with financial decisions. However, profitability is able to moderate the relationship between size company and financial decisions.